Statistical Analysis of Early Childhood Learning Outcomes: Bridging The Gap Between Learning Theories And Islamic Educational Practices - Siti Vania Nuraida; Ema Maesaroh; Kiki Mohammad Iqbal; Rahayu Kariandinata; Tarsono Tarsono (CV. Ulil Albab Corp, 2026)
This study aims to examine the effectiveness of an Islamic Education (PAI) learning model based on the integration of behavioristic, cognitive, and constructivist learning theories on early childhood learning outcomes. The main problem addressed in this research is the dominance of rote-based Islamic learning that fails to provide meaningful learning experiences. This study employed a quantitative approach with a quasi-experimental method using a pretest-posttest control group design. The sample consisted of two groups: an experimental group and a control group in early childhood education settings. Data analysis techniques included normality test, homogeneity test, N-Gain test, and independent sample t-test. The results showed a significant improvement in the experimental group with a posttest average score of 84.7 compared to 74.2 in the control group. The t-test results showed a significance value of 0.000 (< 0.05), indicating a significant effect of the learning model on early childhood learning outcomes. Therefore, the integration of behavioristic, cognitive, and constructivist theories is proven effective in improving Islamic Education learning outcomes in early childhood education.